(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
This article examines three parchment leaves originally belonging to two 13th-century notarial registers. These leaves were reused in the 15th century as guard-leaves for two manuscripts preserved in the Vatican Library, namely Vat. Lat. 1469 and Vat. Lat. 1979. The three leaves contain fifteen imbreviatuarae written by the notary Giovanni Pandulfi in Sutri in 1262 and another year of the second half of the 13th century. The importance of these texts lies in the fact that they constitute the only extant testimony of 13th-century notarial protocols from Sutri. Furthermore, in Lazio, only two other fragments of notarial protocols from that period exist. Therefore, they contribute to the knowledge of notarial registration practices in the early phase, and their discovery also increases our understanding of reusing discarded documents.